Enhancement in dielectric, ferroelectric, and electrostrictive properties of Pb(Mg1/3Nb2/3)0.9Ti0.1O 3 ceramics by CuO addition - Promsawat M. (2014)
Effects of CuO on dielectric, ferroelectric and electrostrictive properties of Pb(Mg1/3Nb2/3)0.9Ti0.1O 3(PMNT) ceramics were studied. The PMNT/xCuO (with x = 0, 0.2, 0.4, 2.0 and 4.0 mol.%) ceramics were prepared by using solid state reaction and sintering process. It was found that the pseudo-cubic lattice parameter, a, gradually increased while the angle α decreased with increasing CuO content. Maximum dielectric constant showed a decreasing trend with increasing CuO with an abrupt increase in value at x = 2.0 mol.%. The temperature of maximum dielectric constant and depolarization temperature tended to increase while the diffuseness of dielectric peak decreased with increasing CuO concentration. Remanent polarization and coercive field of pure PMNT sample were ∼1.8 μC/cm2 and 0.6 kV/cm, respectively, which were increased to ∼3.5 μC/cm2 and 1.8 kV/cm when x = 0.2 mol.%. With x > 0.2 mol.%, coercive field gradually decreased with increasing CuO content while remanent polarization did not significantly change. With x ≤ 2.0 mol.%, induced strain and electrostrictive coefficient tended to increase with increasing CuO content, with maximum values of 0.09% (at 10 kV/cm) and 19.90 × 10-16 m2/V2, respectively, for the PMNT/2.0 mol.% CuO sample. An enhancement in polar order of PMNT ceramics due to an addition of CuO was observed. © 2013 Elsevier B.V. All rights reserved.